The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1366/000370203322005364
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopic Monitoring of the Diffusion Process of Deuterium-Labeled Molecules in Wood. Part I: Softwood

Abstract: The diffusion process of several molecules (D2O, n-butanol (OD) and t-butanol (OD)) in softwood (Sitka spruce) was investigated by means of a deuterium exchange method and Fourier transform near-infrared (FT-NIR) polarization spectroscopy. The location of OH groups in different states of order of cellulose in wood was clarified by analyzing the FT-NIR transmission spectra ranging from 7200 to 6000 cm(-1). Four absorption bands were assigned to 2 x v(OH) absorptions of the amorphous regions, OH groups in semi-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 16 publications
(11 reference statements)
2
91
0
Order By: Relevance
“…The second-derivative spectra of the untreated wood (solid line) displayed peaks in some regions with stronger intensities. However, the spectra of the ethanol-extracted samples (dotted line) showed less absorption, such as for the bands at 5976 cm -1 and 4686 cm -1 , which were determined to be closely related to the aromatic ring in the lignin and extractives (Michell et al 1996;Tsuchikawa and Siesler 2003;Workman and Weyer 2007;Sandak et al 2011). Overall, these combined results confirmed that the CE extractives were changed by the extraction pretreatment.…”
Section: Nir Model Developmentmentioning
confidence: 64%
See 1 more Smart Citation
“…The second-derivative spectra of the untreated wood (solid line) displayed peaks in some regions with stronger intensities. However, the spectra of the ethanol-extracted samples (dotted line) showed less absorption, such as for the bands at 5976 cm -1 and 4686 cm -1 , which were determined to be closely related to the aromatic ring in the lignin and extractives (Michell et al 1996;Tsuchikawa and Siesler 2003;Workman and Weyer 2007;Sandak et al 2011). Overall, these combined results confirmed that the CE extractives were changed by the extraction pretreatment.…”
Section: Nir Model Developmentmentioning
confidence: 64%
“…Band 1 located at 5976 cm -1 was assigned to the Car-H 1 st stretching vibration of aromatic groups in the lignin (aromatic skeletal, or aromatic C-H in lignin) (Workman and Weyer 2007;Tsuchikawa and Siesler 2003;Sandak et al 2011). Band 2 located at 5936 cm -1 was assigned to the Car-H 1 st stretching vibration of the aromatic ring associated with aromatic skeletal structures in the lignin (Tsuchikawa and Siesler 2003;Workman and Weyer 2007;Sandak et al 2011). Band 3 located at 5848 cm -1 was assigned to the C-H 1 st stretching vibration of furanose/pyranose in the hemicellulose (Yonenobu and Tsuchikawa 2003).…”
Section: Nir Model Developmentmentioning
confidence: 99%
“…In these absorption bands, all bands except for 5220 cm -1 assigned to water [18], are associated with cellulose among the wood components. The absorption bands at 7000, 5464 and 4280, and 4890-4620 cm -1 are assigned to amorphous regions in cellulose, semi-or crystalline regions in cellulose, and cellulose, respectively [8,18,19]. The absorption band of 4404 cm -1 is assigned to cellulose and hemicellulose, and 5980 cm -1 is the aromatic skeletal area due to lignin [18,20].…”
Section: Anatomical Characteristicsmentioning
confidence: 99%
“…Brunner et al [6] reported that cluster analysis could be used to distinguish 12 different wood species. Tsuchikawa et al [7] developed a species classification method using NIR spectroscopy combined with Mahalanobis's generalized distance, and investigated the diffusion process of deuterium-labeled molecules using NIR spectroscopy [8]. The most widely used multivariate analysis techniques for species classification are principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Eq. (8), a second order weight factor (1/n) 2 contributes to the second derivative, which leads to the fact that several papers have utilized the first and second derivative for feature description of NIR spectra [1,17,[36][37][38][39][40][41][42][43]. In general, the 1 st derivative is explained by a simple measure of the slop of the spectral curve at every point, and 2 nd derivative is a measure of the change in the slop of the curve.…”
Section: Derivative Coefficients As Feature Representation In Ft-nirmentioning
confidence: 99%